Investigating the preparation process of excellent Cu3VSe4 absorption layer prepared by amine-thiol system - Yanqing Liu; Yanchun Yang; Junting Ren; Guonan Cui; Xin Zhao; Rui Wang; Lulu Bai; Chengjun Zhu (Arabian Journal of Chemistry, 2024)
Cu3VSe4 material has become a new kind of photovoltaic absorber due to its optical bandgap matching light-absorbing, abundant elements in crust, and high light absorption coefficient. Here, we prepared Cu3VSe4 thin films by amine-thiol method and investigated the preparation process of excellent Cu3VSe4 absorption layer for the first time. The effects of various Cu/V ratios on the morphology, structure, and electrical properties of the films are studied. XRD and Raman results show that pure-phase Cu3VSe4 films are obtained with the Cu/V ratios lower than 2.9. SEM results simply adjusting the Cu/V ratio cannot obtain a compact selenized Cu3VSe4 thin films. The best crystallinity of thin film with 2.8 of Cu/V ratio is named as Cu2.8VSe4 and selected as the representative. Though optimizing the selenization conditions, a dense morphology and good electrical properties of the absorption layer can be prepared under 570 °C of the high-temperature process. Our findings can lay the favorable foundation for high-efficiency Cu3VSe4 devices.